Efeito do genótipo, ambiente e suas interações em características agronômicas e de qualidade em cevada cervejeira no sul do Brasil - Borowski, Daniel Zancanaro (2012)
Barley is a winter cereal that ranks fourth in order of economic importance in the world. In Europe and North America it is a culture with multiple purposes, used by the brewing industry, animal feed and food industry. In Brazil, as there are alternatives with lower cost of production for feed and food, more than 95% of the barley is grown for brewers. This fact makes all the breeding programs of barley in Brazil be focused on brewing quality research, because it is crucial in launching a new cultivar. Currently we can observe undesirable variations in quality brewing barley produced in Brazil. The main causes of this variation includes the occurrence of adverse weather conditions, by high levels of rainfall at harvest and late frosts, which detracted from the quality of the product. For the indication of cultivars most suitable for each region, minimizing problems of quality and enhancing grain yield, this study was conducted to evaluate the effect of genotype, environment and their interactions on agronomic characteristics and quality of six cultivars of barley (BRS Elis, BRS Cauê, MN 743, MN 610, BRS 195 and Scarlett) at four locations (Júlio de Castilhos, Lagoa Vermelha, Passo Fundo and Victor Graeff) in Rio Grande do Sul, in 2010. It was used randomized block design with four replications. The barley cultivars showed significant genotype x environment interaction for several traits like grain yield, spikes m-2, thousand kernel weight, germination and extract content. The cultivars showed stability in germination and grain yield, and the component number of grains m-2 was more important than the thousand grain weight, for the yield of barley. The BRS Cauê excelled in quality results. The conditions of Victor Graeff and Passo Fundo were more favorable for agronomic traits and yield components, while Lagoa Vermelha was more favorable for quality characteristics.